2018
DOI: 10.1002/ange.201713036
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sequence‐Controlled Antimicrobial Polymers: Effect of Polymer Block Order on Antimicrobial Activity

Abstract: Synthetic polymers have shown promise in combating multidrug-resistant bacteria. However,the biological effects of sequence control in synthetic antimicrobial polymers are currently not well understood. As such, we investigate the antimicrobial effects of monomer distribution within linear high-order quasi-blockc opolymers consisting of aminoethyl, phenylethyl, and hydroxyethyl acrylamides made in aone-pot synthesis approach via photoinduced electron transfer-reversible addition-fragmentation chain transfer po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 75 publications
0
36
0
Order By: Relevance
“…Our group has also implemented a similar approach to elucidate the key role of monomer sequence on activity of polymers in antimicrobial applications. [85] The ability to produce and screen a large range of structures under moderate conditions in these systems decreases the time required for experimentation through to analysis; such protocols show promise for the fast-tracked discovery of new polymers for a range of bio-applications. [84a]…”
Section: Applications Of Oxygen Tolerance Photopolymerizationmentioning
confidence: 99%
“…Our group has also implemented a similar approach to elucidate the key role of monomer sequence on activity of polymers in antimicrobial applications. [85] The ability to produce and screen a large range of structures under moderate conditions in these systems decreases the time required for experimentation through to analysis; such protocols show promise for the fast-tracked discovery of new polymers for a range of bio-applications. [84a]…”
Section: Applications Of Oxygen Tolerance Photopolymerizationmentioning
confidence: 99%
“…[1][2][3] Recent examples have demonstrated that even relatively simple monomer sequences can affect polymer behaviors. [4][5][6][7][8][9][10] While significant advances have been made in the past decade to encode primary structures of polymers via solid-phase synthesis, 11,12 iterative synthesis, [13][14][15][16] or the use of biological templates, 17 these approaches are often limited in the length of polymers or oligomers that can be prepared and the synthetic scalability while requiring complex chromatographic purification. Periodic polymer sequences can be accessed via alternating polymerizations, [18][19][20][21][22] multicomponent reactions, [23][24][25] polymerization of short sequences, 26,27 and exponential growth methods.…”
Section: Introductionmentioning
confidence: 99%
“…44, Checkerboard plots of tested combinations against two Gram-negative bacteria Pseudomonas aeruginosa PAO1 and Escherichia coli K12 are represented in Figures S3 and S4 (SI), Gram-positive bacteria were not included in this study as the antimicrobial activity of P is better against Gram-negative bacteria. 37 The mechanism behind the synergistic interactions is complicated; however, the mode of action of individual components might explain the observed synergy. When used in combination with other compounds that act on intracellular targets, membrane-targeting compounds are expected to modulate the intracellular drug concentration.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of our experience in the development of antimicrobial polymers [35][36][37] and the potential benefits of combination therapy, [38][39][40][41] we herein investigate the efficacy of an antimicrobial platform based on our lead synthetic antimicrobial polymer 35,39 in combination with different classes of commercially available antibiotics (e.g., doxycycline from the tetracycline family, as depicted in Figure 1). The potency of these combinations is investigated via checkerboard assay and the synergistic combinations are further studied in terms of bactericidal activity and resistance development in bacteria.…”
mentioning
confidence: 99%